2005
DOI: 10.1179/crn.2005.029
|View full text |Cite
|
Sign up to set email alerts
|

Does Head Posture Have a Significant Effect on the Hyoid Bone Position and Sternocleidomastoid Electromyographic Activity in Young Adults?

Abstract: The aim of this study was to evaluate the associations between head posture (head extension, normal head posture, and head flexion) and anteroposterior head position, hyoid bone position, and the sternocleidomastoid integrated electromyographic (IEMG) activity in a sample of young adults. The study included 50 individuals with natural dentition and bilateral molar support. A lateral craniocervical radiograph was taken for each subject and a cephalometric analysis was performed. Head posture was measured by mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1
11

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 19 publications
2
15
1
11
Order By: Relevance
“…Não foram encontradas associações entre posturas de cabeça anteroposteriores e ativação maior de musculatura supra-hióidea, ou seja, posturas do osso hióide no sentido anteroposterior, de acordo com [2].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Não foram encontradas associações entre posturas de cabeça anteroposteriores e ativação maior de musculatura supra-hióidea, ou seja, posturas do osso hióide no sentido anteroposterior, de acordo com [2].…”
Section: Discussionunclassified
“…A postura da cabeça é um fator significativo nos estudos de movimentos do osso hióide e da função dos músculos supra e infra-hióideos [1] [2].…”
Section: Introductionunclassified
“…Most of the studies about hyoid bone position have shown that changes in mandibular position are related to hyoid bone changes and that hyoid bone position adapts to anteroposterior changes in head posture (8,9,10 Hyoid kemik mandibulaya geniohyoid, anterior digastrik ve milohyoid kaslar aracılığıylabağlıolduğundan,mandibulanın konumunu değiştiren tüm ortodontik işlemlerin hyoid kemiğin pozisyonunda da değişimlerenedenolabileceğibirçokçalışma ilegösterilmiştir (8,9,10).…”
Section: Hyoidboneheadpostureand Craniofacialmorphologyunclassified
“…Becausethehyoidboneisattachedtothe mandibula by geniohyoid, anterior digastric andmylohyoidmuscles,ithasbeenshownby severalstudiesthatallorthodonticprocesses those change the position of the mandibula mayalsocausechangesinthepositionofthe hyoidbone (8,9,10).…”
Section: A-positional Alterations Occurring At the Hyoid Bone And In mentioning
confidence: 99%
“…-the neuromuscular activity of neck and face muscles seems to influence corporal or bodily posture according to many studies 25,65,66,84 , but, according to another one, do not 99 ;…”
Section: ---A Few Commentsmentioning
confidence: 99%